EFFECT OF LEAD ACETATE ON SPERM MORPHOLOGY AND TESTIS OF WISTAR ALBINO RATS - SUJATHA, K; SRILATHA, C H; ANJANEYULU, Y; RAO, T S CHANDRASEKHAR; SREENIVASULU, D; AMARAVATHI, P (The Indian Journal of Animal Reproduction, 2011)
In the present study different doses of lead acetate was used to know the effect on testis, sperm count,sperm morphology in different experimental groups. 108 male wistar rats were divided into three equal groups (I, II&111) i.e. each group contains 36 rats. Group I kept as control. Group II & Ill rats were orally administered leadacetate@ 60 mgs & 30mgs /kg. bwt / 3 days in a week for 90 days. Every fortnight from each group rats weresacrificed with anesthetic ether and epididymis collected for sperm count, testes for measurement of testicularweight and pieces of testis fixed in Bevin's fixative for histopathological and histochemical studies. The studyrevealed that lead acetate caused a dose dependant reduction in sperm count, testicular weight, and abnormalsperm count was increased significantly when compared to control. Hisopathologically testis shows necrosis ofseminiferous tubules. Complete separation and disappearance of seminiferous tubular epithelium. Lead also causedreduction in testicular alkaline phosphatase activity.
Keywords: Lead poisoning; Testis; Sperm morphology; Histopathology; Histochemistry; Albino rats